A comparison of Jacobian-based methods of inverse kinematics for serial robot manipulators - Dulęba, Ignacy; Opałka, Michał (Zielona Góra: Uniwersytet Zielonogórski)
The objective of this paper is to present and make a comparative study of several inverse kinematics methods for serial manipulators, based on the Jacobian matrix. Besides the well-known Jacobian transpose and Jacobian pseudo-inverse methods, three others, borrowed from numerical analysis, are presented. Among them, two approximation methods avoid the explicit manipulability matrix inversion, while the third one is a slightly modified version of the Levenberg-Marquardt method (mLM).
Keywords: serial manipulator; inverse kinematics; Jacobian methods; comparisons; applications